On the choice of stress–strain variables for unsaturated soils and its effect on plastic flow. (September 2018) - Gallipoli, Domenico; Grassl, Peter; Wheeler, Simon; Gens, Antonio
Abstract: The net stress plus suction and the average skeleton stress plus modified suction are two alternative sets of energetically consistent stress variables for modelling the hydro-mechanical behaviour of unsaturated soils. When used in conjunction with their work-conjugate strains, both sets of stress variables correctly calculate the first-order term of the hydro-mechanical work input into a soil element subjected to infinitesimal changes of deformation and water content. They therefore also correctly calculate the increment of internal energy along a given stress–strain path, that is the integral of the first-order term of the infinitesimal work input. This paper shows, however, that the above two sets of stress variables lead to different values of the second-order term of the hydro-mechanical work input. They are therefore no longer equivalent with respect to other aspects of material behaviour governed by the second-order work such as the flow rule of elasto-plastic models. The flow rule assumes the normality between plastic strains and equipotential surfaces defined in the conjugate stress–strain space. This normality is however lost when an elasto-plastic model originally formulated in terms of net stress plus suction is recast in terms of average skeleton stress plus modified suction (or vice versa) by means of standard mapping relationships between stress variables. To restore normality in both stress spaces, it is necessary to impose specific forms of elastic and plastic behaviour. Highlights: Net stress/suction and skeleton stress/modified suction are alternative stress sets. Second-order work takes different values depending on chosen stress set. Normality of plastic flow rule is lost when mapping between stress sets. Consistency across stress sets is recovered if specific material laws are assumed.